1998
DOI: 10.1002/(sici)1097-010x(19980615)281:3<228::aid-jez9>3.3.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure and lectin cytochemistry of the cloacal kingsbury's glands in the male newt Triturus marmoratus marmoratus

Abstract: The aim of this study was the morphological and histochemical characterization of Kingsbury's glands in the male newt Triturus marmoratus marmoratus in the pre-reproductive and post-reproductive period of the testicular cycle, using light and electron microscopy and lectin histochemistry. The Kingsbury's glands are a small group of tubular glands that surrounds the cloacal tube. In the pre-reproductive period, Kingsbury's glands showed a cuboidal epithelium that was partially surrounded by myoepithelial cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1999
1999
2002
2002

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Consistent with this idea is the expression of different glycoconjugates by distinct functional classes of cells in the visual (Chan et al, 1999), respiratory (Kasper and Singh, 1995;BurkhardtHolm, 1997;Dorscheid et al, 1999), gustatory (Zeng et al, 1995), olfactory (Taniguchi et al, 1993;Shnayder-Shapiro et al, 1995;Nakajima et al, 1998;, gastrointestinal (Sato and Spicer, 1982;Falk et al, 1994;Ge et al, 1998;Gebhard and Gebert, 1999;Poorkhalkali et al, 1999), reproductive (Zhou et al, 1994;Arenas et al, 1998;Romo et al, 1999), and immune (Clark et al, 1995;Sharma et al, 1996;Foster et al, 1998) systems in a variety of mammalian species.…”
Section: Discussionmentioning
confidence: 94%
“…Consistent with this idea is the expression of different glycoconjugates by distinct functional classes of cells in the visual (Chan et al, 1999), respiratory (Kasper and Singh, 1995;BurkhardtHolm, 1997;Dorscheid et al, 1999), gustatory (Zeng et al, 1995), olfactory (Taniguchi et al, 1993;Shnayder-Shapiro et al, 1995;Nakajima et al, 1998;, gastrointestinal (Sato and Spicer, 1982;Falk et al, 1994;Ge et al, 1998;Gebhard and Gebert, 1999;Poorkhalkali et al, 1999), reproductive (Zhou et al, 1994;Arenas et al, 1998;Romo et al, 1999), and immune (Clark et al, 1995;Sharma et al, 1996;Foster et al, 1998) systems in a variety of mammalian species.…”
Section: Discussionmentioning
confidence: 94%
“…Based on ultrastructural and morphological characteristics, it has been suggested that the urodele cloacal glands are homologous to some glands and ducts of the mammalian reproductive systems in mammals (Norris et al, 1989). In particular, the ventral glands of T. marmoratus have been compared with the bulbourethral glands, while the Kingsbury's glands show homologies with the epididymis (Romo et al, 1998). The present results suggest that pelvic glands of T. marmoratus are homologous to the prostate and seminal vesicles.…”
Section: Discussionmentioning
confidence: 99%